AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY AT MTS SUNAN GIRI SUMBERJAYA - Hanif Maulaniam Sholah; Hilda Qotrun Nada (Universitas Al-Qolam Malang, 2024)
This study used a qualitative descriptive research. The object is 15 students of 7 (Seven) grade of junior high school for the academic year 2022/2023 at Mts Sunan Giri Sumberjaya who will be interview and given a questionnaire To find out the factors that influence the difficulty of speaking in English and To find the way to reduce experiencing speaking anxiety. The result of the research findings demonstrated that many students experience speaking anxiety Speaking anxiety can hinder the process of learning English, therefore students need to think positive thinking when learning that making mistakes is a natural thing when learning and failure is a process towards better learning. Teachers are expected to pay students' attention and to be able to create an enjoyable classroom atmosphere and motivate students to be confident in speaking English. Keywords: Speaking, Anxiety, Student.